Serum Lactate Level in Early Stage Is Associated With Acute Kidney Injury in Traumatic Brain Injury Patients - Wang, Ruoran; Wang, Shaobo; Zhang, Jing; He, Min; Xu, Jianguo (Frontiers in Surgery, 2022)
Background Acute kidney injury (AKI) is a common complication in the clinical practice of managing traumatic brain injury (TBI) patients. Avoiding the development of AKI is beneficial for prognosis of TBI patients. We designed this study to testify whether serum lactate could be used as a predictive marker of AKI in TBI patients. Materials and methods 243 TBI patients admitted to our hospital were included in this study. Univariate and multivariate logistic regression analysis were utilized to analyze association between lactate and AKI. Receiver operating characteristics curves (ROC) were drawn to verify the predictive value of lactate and the logistic model. Results AKI group had higher age (p=0.016), serum creatinine (p<0.001), lactate (p<0.001) and lower GCS (p=0.021) than non-AKI group. Multivariate logistic regression showed age (OR=1.026, p=0.022), serum creatinine (OR=1.020, p=0.010), lactate (OR=1.227, p=0.031), fresh frozen plasma (FFP) transfusion (OR=2.421, p=0.045) and platelet transfusion (OR=5.502, p=0.044) were risk factors of AKI in TBI patients. The area under the ROC curve (AUC) value of single lactate and predictive model was 0.740 and 0.807, respectively. Conclusion Serum lactate level in early phase is associated with AKI in TBI patients. Lactate is valuable for clinicians to evaluate the probability of AKI in TBI patients.